PARTISIPASI MASYARAKAT TERHADAP PERENCANAAN PEMBANGUNAN INFRASTRUKTUR DI DESA SIPODECENG KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Pertiwi, A; Sellang, Kamarudding; Ikbal, Muhammad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the principles of community participation in infrastructure development planning in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency. The population in this study was 3,713 people in Sipodeceng Village, while the sample in this study was 98 people determined using the Slovin formula..This type of research is descriptive research with a quantitative research design. Data collection techniques were carried out through observation, interviews and questionnaires. The data analysis technique used was descriptive analysis, data quality testing and simple linear regression and hypothesis testing using the SPSS version 16 program. The research results showed that, the research results showed that community participation in infrastructure development planning with 6 indicators (thoughts, energy, thoughts and energy, skills, goods and money). which has an average percentage value of 71%. or can be categorized as "Good". The average percentage value of the influence of community participation on infrastructure development planning with indicators (coordination, synchronization, consistency, participation and resources efficiently, effectively and fairly) is 76% or can be categorized as "Good".